PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN NON MEDIS DI RUMAH SAKIT ISLAM PDHI YOGYAKARTA - Nugroho, Himawan Agung (LPPM Akademi Manajemen Administrasi Yogyakarta, 2021)
In this research, researchers want to know what factors that can affect the performance of employees especially in a hospital which is a health facility. So that writers do associated research the influence of motivation and style of non medical employee performance in Islamic hospital of PDHI Yogyakarta. In this research the use writers and quantitative methods got that koefisiensi regression value of the motivation variable (X1) of 0,392 And value the regression coefficient multiple for variable leadership style (X2) of 0,184. There are significant influence between variables motivations (X1) and variable leadership style (X2) To employee performance (Y). So that, Ho refused and Ha accepted. This means that motivation (X1) Shown to have a positive effect on performance (Y) employees of in hospital of Islamic hospital of PDHI Yogyakarta. This means that if the incentives given the better, will improve employee performance in Islamic hospital of PDHI Yogyakarta